Global liquidity and financial flows to developing countries : new trends in emerging markets and their implications - Chandrasekhar, C. P. (UN New YorkUS, 2008)
Examines the surge in capital flows into developing countries and looks at the qualitative changes in financial integration that are accompanying this surge. Focuses on the impact that this surge is having on financial volatility and vulnerability, macroeconomic management and growth in countries that have been 'successful' in attracting such flows.